Pattern Recognition: Impact of Exercises Modes on Developing a Small Ball Throwing Skill in Boys Aged 8 - Sergii Iermakov; Olha Ivashchenko; Oleg Khudolii; Sergii Chernenko; Viktoriia Veremeenko; Bohdan Zelenskyi (OVS LLC, 2021)
The purpose of the study was to determine the impact of exercises modes on developing a small ball throwing skill in boys aged 8.  Materials and methods. The study participants were 21 boys aged 8, who were randomly divided into three groups of 7 people. The children and their parents were fully informed about all the features of the study and gave their consent to participate in the experiment. The study examined the influence of the number of repetitions on the effectiveness of teaching boys aged 8 throwing a small ball at a target. A pedagogical experiment examined the influence of 6, 12, and 18 repetitions with a 60-second rest interval on the increase in the level of proficiency in exercises of boys aged 8. In the first group, the boys repeated the task 6 times with a rest interval of 60 s, in the second group - 12 times with a rest interval of 60 s, in the third group 18 times with a rest interval of 60 s. When teaching throwing exercises during the class, the study evaluated the level of proficiency by the alternative method ("performed", "failed") and calculated the probability of exercise performance (p = n/m, where n is the number of successful attempts, m is the total number of attempts).  In teaching boys aged 8, the method of algorithmic instructions was used. The next exercise started after three successful attempts. Throwing a ball at a vertical target was taught. The study materials were processed by the IBM SPSS 20 statistical analysis software. During discriminant analysis, a prognostic model for group membership was created.  Results. Discriminant analysis made it possible to determine the impact of the number of repetitions on the effectiveness of developing the skills of throwing a small ball at a target; answer the question as to how significantly the modes of repetitions differ by the effectiveness of motor skills development, what class the object belongs to based on the values of discriminant variables. Conclusions. Based on the analysis of group centroids, it was found that in boys aged 8, six repetitions of the exercise (6 sets one time with a rest interval of 60 s) significantly influence the increase in the level of proficiency in exercises during physical education lessons. The results of group classification show that 85.7% of the original grouped observations were classified correctly.